How clinical nurse and midwifery consultants optimise patient care in a tertiary referral hospital. Issue 19 (8th February 2014) - Atsalos, Christine; Biggs, Karen; Boensch, Sabine; Gavegan, Fiona Lee; Heath, Susan; Payk, Marlene; Trapolini, Grace
<x xml:space="preserve">Abstract</x> Aims and objectives To develop new insights into the phenomenon of clinical nurse/midwifery consultant clinical effectiveness in a tertiary referral hospital. Background International studies identify the pivotal role clinical nurse/midwifery consultants play in patient outcomes. There remains, however, a significant deficit in our knowledge of how these, or other advanced practice nurses and midwives, apply their extensive experience, ontological understandings and tacit knowledge to the enhancement of patient outcomes in complex healthcare environments. Design This study was underpinned by the principles of Heideggerian hermeneutic phenomenology. Methods Recruitment involved expressions of interest distributed hospital‐wide to clinical nurse/midwifery consultants. Inclusion criteria specified a minimum of three years' experience. Fifteen clinical nurse/midwifery consultants, representing a broad range of specialties, were interviewed. Preliminary descriptive analysis of transcribed data was followed by in‐depth hermeneutic analysis. Results The findings comprise four themes: walking beside the patient, anticipating the unexpected, pushing through barriers and leading within a complex system. These themes highlight how clinical nurse/midwifery consultants significantly influence pre‐existing trajectories of patient care delivery through context‐appropriate strategies. Conclusion This study introduces new insights into the meanings advanced practice nurses and midwives develop from their engagements with patients and how these meanings inform clinical decisions. The paper accomplishes this by drawing on Heideggerian philosophical concepts such as ontological understandings, authenticity and care. It also casts light on the participants' shared understandings of how to synergise expectations within the team. Relevance to clinical practice The significance of this paper lies in the uncovering of ontological understandings and tacit knowledge of how consultant nurses and midwives optimise patient care delivery in challenging situations. The findings indicate, however, that the value of these internationally established roles is yet to be fully realised. The paper concludes by recommending strategies to assist newly appointed clinical nurse/midwifery consultants transition into these demanding autonomous roles.